A New Find of a Falchion from Central Poland - Piotr Strzyż; Kalina Skóra (Fasciculi Archaeologiae Historicae)
This paper discusses a find of a falchion from the neighbourhood of Gieczno in the Łódzkie Voivodeship. This artefact comes from a sequestration of the collection of an illegal treasure hunter. This 15th century falchion with a conventional blade form stands out with its hilt which is provided with a cap-like pommel, and first of all with a scales rivet which is shaped as an ornamental rosette.